Menasseh ben Israel : a digital collection of seventeenth-century Jewish printing in Amsterdam - De Haas, J. J. M.; Offenberg, Adriaan K.; Ootjers, M. G.; Bibliotheca Rosenthaliana ([Amsterdam] : Amsterdam University Press, 1999)
Collection consisting of more than 11,000 digital images from the Bibliotheca Rosenthaliana collection of 69 editions of books (chiefly first editions) printed by Menasseh ben Israel, one of the first Jewish printers in the Netherlands.
System requirements: 486 processor; 8MB RAM; Windows 3.11/NT, Macintosh, or Unix; 10MB available hard disk space; Web browser supporting frames; TIFF viewer.
Title from disc label.
Keywords: Manasseh ben Israel, -- 1604-1657 -- Catalogs; Bibliotheca Rosenthaliana -- Catalogs; Rare books -- Netherlands -- Amsterdam -- Bibliography -- Catalogs; Manasseh ben Israel, -- 1604-1657.